2021
DOI: 10.3390/en14082173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lorentz Force in Thermally Developed Pulsatile Micropolar Fluid Flow in a Constricted Channel

Abstract: This work aimed to analyze the heat transfer of micropolar fluid flow in a constricted channel influenced by thermal radiation and the Lorentz force. A finite difference-based flow solver, on a Cartesian grid, was used for the numerical solution after transforming the governing equations into the vorticity-stream function form. The impact of various emerging parameters on the wall shear stress, axial velocity, micro-rotation velocity and temperature profiles is discussed in this paper. The temperature profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, in Figure 6(c) we can see that as K rises, so does the absolute value of the microrotation vector close to the plates, 20,49 and is therefore obvious that additional viscosity λ emphasizes the characteristics of micropolar fluids. This means that additional viscosity λ emphasizes the small particle microrotation, which particles were embedded in the fluid.…”
Section: Results Analysismentioning
confidence: 97%
See 3 more Smart Citations
“…However, in Figure 6(c) we can see that as K rises, so does the absolute value of the microrotation vector close to the plates, 20,49 and is therefore obvious that additional viscosity λ emphasizes the characteristics of micropolar fluids. This means that additional viscosity λ emphasizes the small particle microrotation, which particles were embedded in the fluid.…”
Section: Results Analysismentioning
confidence: 97%
“…Before we proceed to further analyse and discuss the problem under consideration using the charts, note that Figure 2(a) and (b) illustrate the comparison between velocity profiles for the problem dealt with in this paper and the results obtained in the paper by Umar. 20 Figure 2(a) shows the dependency of the change in velocity profiles based on the changes in the value of the coupling parameter K , whereas Figure 2(b) compares velocity profiles for values K = 0 . 1 and 0.4. The comparisons of dimensionless velocities given in Figure 2(a) and (b), show a very good match.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ali et al (2021c) investigated the micropolar fluid flow in a channel with symmetrical constriction and concluded that the wall shear stress has a direct relation to the magnetic parameter and Reynolds number. Umar et al (2021) extended the work to investigate the heat transfer effects in the presence of thermal radiations. Ali et al (2020b) examined the pulsatile flow of the MP-Casson fluid in a constricted channel and found the Hartmann number to be a significant parameter to control the flow separation region, which appears after the constriction bump along the wall.…”
Section: Introductionmentioning
confidence: 99%